A rare case report of massive ovarian edema - Parthasarathy K. K. A., Akshaya; R., Charumathi; J., Madhumitha; Vijayaraghavan, Bharani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Massive ovarian oedema is a benign ovarian pathology occurs due to partial ovarian torsion and blockage of lymphatic drainage of the ovary. Commonly presents with pain abdomen on and off or abnormal uterine bleeding. Here we report a case of 15 years old girl with spotting per vaginum for 45 days. On examination, revealed 28 weeks size mass arising from pelvis. On further evaluation and blood works, proceeded with surgical management. Histopathological examination revealed benign massive ovarian oedema. However, it’s important to know differential diagnosis for solid ovarian tumours.